(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
This paper presents a photovoltaic system connected to a solid-state transformer (SST). The PVs are integrated into the low-voltage DC (LVDC) link. The SST consists of three stages containing combinations of converters: the modular multilevel converter MMC is employed in the medium voltage (LV) stage, the DC-DC converter is applied in the isolated stage, and a three-phase inverter is utilized in the low voltage (LV) stage. To ensure the smooth integration of PVs, it is essential to maintain a stable voltage at the LVDC level. To this end, the application control of the DC-DC converter must be used. The single-phase shift control (SPS) strategy was adopted. This control strategy maintains DC voltage levels at appropriate values and enables bidirectional power flow. In addition, to optimize the extraction of maximum power from the PVs, a maximum power point tracking (MPPT) technique is applied based on the M5P model decision tree. In parallel, to ensure optimal operation of the SST, a voltage-oriented control (VOC) and voltage capacitor balancing algorithm based on rotating gating signals is implemented for the MMC converter. In contrast, an unbalanced load control is applied to the inverter. The model developed in this study was implemented in MATLAB/Simulink, and the system’s dynamic performance was validated.